Exploring a poorly understood variable: An agenda for classroom research on the age factor. (21st December 2018) - Singleton, David; Pfenninger, Simone E.
Abstract : This article is concerned with age in second language learning. It steers well clear, however, of the well-worn issue of maturational constraints and the intractable problems of locating their consensual offset point and finding indisputable evidence for or against them. Instead we propose something completely different in our agenda for age-related research: a programme on some poorly understoodnon -maturational dimensions of the age factor which will stand some chance of yielding results unlikely to become entangled in theoretical controversy. In other words, the results will, we think, be immediately usable and useful. The topics included in our outlined agenda are: (1) age effects in various dimensions of language teaching and learning (in relation to bilingualism and biliteracy, to different target languages and to Content and Language Integrated Learning (CLIL); (2) what can be observed in respect of second language (L2) learning in the third age; (3) an ecological perspective on age in classroom L2 research methodology; and (4) an exploration of the attitudes of teachers of different-aged L2 learners.